1997
DOI: 10.1042/bj3210227
|View full text |Cite
|
Sign up to set email alerts
|

Glucose induces the translocation of glycogen synthase to the cell cortex in rat hepatocytes

Abstract: After incubation with glucose a dramatic change in the intracellular distribution of glycogen synthase was observed in rat hepatocytes. Confocal laser scanning microscopy showed that glycogen synthase existed diffusely in the cytosol of control cells, whereas in cells incubated with glucose it accumulated at the cell periphery. Colocalization analysis between glycogen synthase immunostaining and actin filaments showed that the change in glycogen synthase distribution induced by glucose correlated with a marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 28 publications
1
64
0
Order By: Relevance
“…We have previously shown that incubation of isolated (5) or cultured hepatocytes (6) with glucose causes the translocation of GS from the cytoplasm to the cell periphery, where initial glycogen synthesis takes place. When added to cultured hepatocytes, DHA has the same effect as glucose on the localization of GS and the pattern of glycogen deposition.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that incubation of isolated (5) or cultured hepatocytes (6) with glucose causes the translocation of GS from the cytoplasm to the cell periphery, where initial glycogen synthesis takes place. When added to cultured hepatocytes, DHA has the same effect as glucose on the localization of GS and the pattern of glycogen deposition.…”
Section: Discussionmentioning
confidence: 99%
“…In isolated hepatocytes, incubation with glucose induces GS activation and intracellular translocation to 1 To whom correspondence should be addressed: Blegdamsvej 3, 2200 Copenhagen N, Denmark. the cell periphery (24). In contrast, in the absence of glucose, GS has been shown to be mainly located inside the nucleus of both cultured liver and muscle cells; however, following addition of glucose GS translocates to the cytosol (25).…”
mentioning
confidence: 93%
“…The fact that several enzymes of glycogen metabolism are directly associated with the glycogen particle has long been appreciated (2,3). More recently, it has been shown that glucokinase (hexokinase IV) and glycogen synthase are sequestered in the nucleus under basal conditions and that both enzymes are translocated to the cytosol upon exposure to nutrients (7,8,11,13,14,28). Furthermore, hepatic overexpression of hexokinase I, an enzyme that is activated by binding to porin in mitochondrial membranes (29), has no effect on activation of glycogen synthase or glycogen deposition, while overexpression of glucokinase impacts both parameters, suggesting that the subcellular localization of these enzymes determines their impact on glycogenesis (9, 10).…”
Section: Figmentioning
confidence: 99%